PF.37 Middle Cerebral Artery Dopplers in a Low-Risk Population. (26th April 2013) - Khalid, A; Higgins, JR; McKenna, DJ
Abstract : Objective: To construct reference intervals for middle cerebral artery Doppler indices in a low-risk population. Study design: This was a prospective, cross-sectional study involving low-risk women attending Cork University Maternity Hospital conducted concurrently with a primary study to construct normograms for fetal biometry. Women were recruited from their first trimester dating scan and randomly allocated to a single scan between 14–40 weeks gestation. Scans were performed by a sole researcher. Gestation was calculated using the estimated due date assigned by dating scan. Recruits were Irish Caucasian women with a singleton pregnancy. Women with conditions affecting placental function including hypertension, pre-eclampsia, renal disease, autoimmune disorders and diabetes mellitus were excluded. Fetuses at risk of anaemia were excluded as were fetuses with congenital anomalies. Middle cerebral artery Dopplers were sampled using the Voluson E8 ultrasound by GE Healthcare. Results: Nine-hundred-and-fifteen women were recruited. Seven-hundred-and-ninety-three women met the inclusion criteria and were scanned as per protocol. Median maternal age was 32 (range 17–44). Median BMI was 24.7 (range 17.1–48.6). Nulliparous women constituted 46.5% (369/793) of recruits, 32.6% (261/793) were expecting their second child, 18.3% (145/793) were expecting their third or fourth child, while only 2.3% (18/793) were grand multiparous. Reference intervals for middle cerebral artery peak systolic velocity (PSV) and pulsatility index (PI) were generated for this population. Conclusion: We have constructed reference interval for middle cerebral artery Doppler indices from 16 to 40 weeks in a low-risk population using up-to-date ultrasound equipment.